Fisheries exploitation in the Indian Ocean : threats and opportunities - Rumley, Dennis, 1947-; Sakhuja, Vijay; Chaturvedi, Sanjay; Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2009)
The book aims to further the debate on the impacts of fisheries policies in the Indian Ocean Region in order to facilitate a new regional policy direction. A key argument of the volume is that ecologically sustainable and socially just development and management of Indian Ocean fisheries require a paradigm shift in the perceptions and policies of major stakeholders. A central policy challenge is to identify a collective regional interest for fisheries and accordingly the development of integrated management policies that link ecology and society and which incorporate individuals, communities, agencies, states and regimes into a holistic cooperative endeavour. Successful ocean governance therefore requires greater inter-state and inter-agency consultation and cooperation, an improvement in linking national initiatives to local action, increased participation of local government and local communities and the enhancement of local capability. In order to achieve this overall goal requires either the enhancement of existing regional institutions or the creation of a new regional body.
Title from publisher's bibliographic system (viewed on 24 Nov 2015).
Keywords: Fishery management, International -- Indian Ocean; Fisheries -- Indian Ocean; Fishery policy -- Indian Ocean